Net-zero energy retrofit of rural house in severe cold region based on passive insulation and BAPV technology. (1st August 2022) - Jiang, Wei; Ju, Zhipeng; Tian, Hangchen; Liu, Yang; Arıcı, Müslüm; Tang, Xiaoying; Li, Qing; Li, Dong; Qi, Hanbing
Abstract: To significantly reduce non-renewable resources and carbon emissions of rural houses, this study investigates to retrofit an existing house into net-zero energy consumption rural house (NZERH). The integral passive energy-saving retrofit and building attached/applied photovoltaic (BAPV) technique are innovatively combined and used in a typical rural house in severe cold areas of China. Self-developed foam cement insulation materials with different thicknesses are added to the envelope to meet the U-values of the two energy-saving standards, and the construction technology of field-cast without demoulding formwork is adopted to increase the integrity and airtightness, and in addition, the external windows are replaced. The photovoltaic (PV) systems at the different positions of the envelope are designed and their power generation is estimated by PVsyst software. The energy consumption and cost of seven combination cases of retrofits and PV systems in NZERH are compared. The results indicate that the insulation thickness of Case R1 and Case R2 is 60 mm (wall) and 50 mm(roof), 240 mm (wall) and 180 mm (roof), respectively. The electrical energy efficiency in the roof (PV1) is the highest, followed by the south facade, and the east facade is the lowest. Case R2 & PV1 of the lower U-value envelope and grid-connected PV system in the roof is the optimal case, which cost is 22826.84 CNY, and the payback period is 5.1 years. The optimization method and results can facilitate the development of clean construction and zero-carbon operation for NZERHs.